2013
DOI: 10.1002/jso.23501
|View full text |Cite
|
Sign up to set email alerts
|

Chemosaturation with percutaneous hepatic perfusion for unresectable metastatic melanoma or sarcoma to the liver: A single institution experience

Abstract: Background Patients with unresectable melanoma or sarcoma hepatic metastasis have a poor prognosis with few therapeutic options. Percutaneous hepatic perfusion (PHP), isolating and perfusing the liver with chemotherapy, provides a promising minimally invasive management option. We reviewed our institutional experience with PHP. Methods We retrospectively reviewed patients with unresectable melanoma or sarcoma hepatic metastasis treated with PHP from 2008 to 2013 and evaluated therapeutic response, morbidity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 18 publications
4
51
0
8
Order By: Relevance
“…7,8,[10][11][12][13] The report from Abbot et al 11 is an update of the study results from Forster et al, 7 so these data are combined in our review. Likewise, some study patients reported in Hughes et al 10 were included in Abbot et al, 11 so we also omitted those case patients from inclusion in our review of the results from Abbot et al 11 and Forster et al 7 No data from Pingpank et al 14 were utilized because this report included preliminary results from a randomized control trial eventually published by Hughes et al…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8,[10][11][12][13] The report from Abbot et al 11 is an update of the study results from Forster et al, 7 so these data are combined in our review. Likewise, some study patients reported in Hughes et al 10 were included in Abbot et al, 11 so we also omitted those case patients from inclusion in our review of the results from Abbot et al 11 and Forster et al 7 No data from Pingpank et al 14 were utilized because this report included preliminary results from a randomized control trial eventually published by Hughes et al…”
Section: Literature Reviewmentioning
confidence: 99%
“…1 Hepatic metastases can also co-occur with many other malignancies, such as breast cancer, renal cell cancer, cutaneous melanoma, and soft-tissue sarcoma. 7,8 For patients with unresectable liver-dominant disease, multiple strategies for liver-directed therapy have been developed, including hepatic artery chemoembolization, radioactive bead embolization, hepatic arterial infusion, isolated hepatic infusion, and chemosaturation with percutaneous hepatic perfusion. 3 In Europe, chemosaturation with percutaneous hepatic perfusion was commercially launched in 2012, and a second-generation, high-efficiency filter was approved for use in conjunction with a proprietary hepatic delivery system that same year.…”
Section: Introductionmentioning
confidence: 99%
“…Another trial described by Forster et al [13] retrospectively reviewed patients treated with PHP at their single institution over a 7 years period. The patients included those with unresectable melanoma or sarcoma hepatic metastases.…”
Section: Moffitt Cancer Center Experiencementioning
confidence: 99%
“…Nine of 10 (90%) patients treated had stable disease (SD) or a PR, with a median partial response of a 33% decrease in tumor burden from baseline. [13] The median follow up for the evaluation was 11.5 months in which the hepatic progression free survival (hPFS) was 240 days. At last 60% of the patients treated at the institution died from their disease.…”
Section: Moffitt Cancer Center Experiencementioning
confidence: 99%
See 1 more Smart Citation